Effect of Active Compounds for Quercus Fruit on Some Biochemical Parameters and Tissue Aorta in Induced Atherosclerosis Rats - Taha, Intisar (Scientific Journal for Faculty of Science-Sirte University, 2022)
This research included extractions of the active compounds from Quercus fruit, the identification of active compounds extract by using the capillary gas chromatography technique CGC and with high-performance liquid chromatography technology HPLC. The active dose of the aqueous extract (250 mg/kg) was studied in animals after induced arteriosclerosis with cholesterol (500mg/kg) dissolved in coconut oil for two weeks. The effect of the extracts oil, poly phenols, and at 7, 37.5, and 10 mg/kg respectively were studied also. The results showed a significant (P≤0.05) increase in catalase activity and the level of high density lipoprotein-cholesterol (HDL-C), However, there was a significant (P≤0.05) decrease in the high plasma kallikrein, caspase-3, cholesterol, triglycerides, and low-density lipoprotein cholesterol LDL-C in induced atherosclerosis rats treated with all extracts compared with affected control with the active extracts (oil, poly phenols) during the first and second week. The tissue aorta examination in the group of animals treated with the active extracts (aqueous, oily, flavonoid) after two weeks of the treatment showed that large parts of the tissues of the aorta were healed close to the normal state compared to the group of animals induced with atherosclerosis untreated whose tissues contained on thickenings and foam cells.